FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENDERITA HIV/AIDS MENGONSUMSI OBAT ANTIRETROVIRAL (ARV) DI KLINIK VOLUNTARY COUNSELING AND TESTING (VCT) RSUP H. ADAM MALIK MEDAN TAHUN 2014 - nanda safira; Rahayu Lubis; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT The success of Antiretroviral Therapy (ART) depends on maintaining a high level of adherence, at least 95% of all doses shouldn’t be forgotten. Non-adherence is associated with the emergence of resistance to HIV that can allow HIV remains replicate. The cumulative number of people who were eligible for ART but not yet started the therapy at Adam Malik Hospital in Medan is 993 people out of 3.525 people (28%), and cumulative number of absentees and failed to follow-up>3 months were 711 people out of 2.532 people (28%) up to April 2015. This research is Cross Sectional study in order to know the factors associated with adherence to ARV consumption towards HIV-infected individuals at Adam Malik Hospital. The sample size was 65 people by consecutive sampling. Data collected through medical records, observation and an interview using questionnaires. Data analysis included descriptive study, Chi Square, Exact Fisher, and Logistic Regression by using STATA software. The result shown that adherence was 28 patients (43,08%) and non-adherence was 37 patients (56,92%). The variables which associated to adherence are job, saturation, stigma at health services, and health insurances. Results of logistic regression test showed that saturation p=0,080 with Prevalence Ratio (PR) 6,20, health insurance (p=0,015; PR 5,00;), and job (p=0,062; PR 0,216) which had dominant association with adherence to ARV consumption at Adam Malik Hospital in Medan. The adherence at Adam Malik Hospital was not optimal, it’s necessary to find a way out to reduce the saturation such as modern HIV treatment which could work well with adherence below 95% so the chances of the adherence in patients HIV/AIDS consuming ARV could be increased.. Keywords: adherence, saturation, health insurance, job